Unerine fibrosis in young patients: clinical and pathogenetic - I. S. Sidorova; A. L. Hunanyan; E. A. Kogan; T. D. Guriev (IRBIS LLC, 2016)
Detailed clinical and morphological study was undertaken on 101 young patients (age 20-30) diagnosed with Uterine fibrosis (the average patient age was 24,7±1,5 years). From the medical history, integrated clinical and morphological study, immunological analysis it was proved to exist two seldom forms of myomatous nodes at a young age: simplefibroid and invasive fibroid, that prevails. The growth originates in a vessel wall from the progenerating muscle cells with relatively high Ki-67 expression, high expression of growth factors and formation of new micro vessels (СD-34). These muscle cells have a very low apoptosis activity that determines the fast proliferation of cells (invasive fibroid).